10h=-5(-h+6)

Simple and best practice solution for 10h=-5(-h+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10h=-5(-h+6) equation:



10h=-5(-h+6)
We move all terms to the left:
10h-(-5(-h+6))=0
We add all the numbers together, and all the variables
10h-(-5(-1h+6))=0
We calculate terms in parentheses: -(-5(-1h+6)), so:
-5(-1h+6)
We multiply parentheses
5h-30
Back to the equation:
-(5h-30)
We get rid of parentheses
10h-5h+30=0
We add all the numbers together, and all the variables
5h+30=0
We move all terms containing h to the left, all other terms to the right
5h=-30
h=-30/5
h=-6

See similar equations:

| 500(2)x^=16,000 | | 2(x-4)=2+3(x+6) | | -24h=720 | | -2y-4=-y+8 | | 2x-26=4x-61=x+15 | | -6a–2a=-64 | | 5n-33=9n-81 | | 2x+1=6x+30 | | 8(3n-9)-2n=9n-7 | | 2x-26=4x-61 | | 7x-3(x+1)=x-12 | | 7=z–9 | | 8x-15=2x+6 | | –6s=–s+5 | | 13-8m-12=61 | | 1/3+2/3(3s+1)=1–s+2/3 | | 4x+5=5(x-1)+x | | 8=-2(r+-5) | | 1/3(24p=66)=3p+43 | | 13+23(3s+1)=1–s+23 | | p÷-9=12 | | 78+.4x=82 | | 14/15=42/x | | -2(1-1x)-3(1x+1)=0 | | 82+.4x=78 | | 6=p-30 | | 6z-7=37 | | 12x-16=4(3x+8) | | 1/5(10-5x)=1/3(-3x+6) | | -30h=-150 | | 8+12p=18 | | f+59=85 |

Equations solver categories